GRAIN REFINEMENT TECHNIQUES TO REDUCE BIODEGRADATION RATE OF MAGNESIUM ALLOY AS A POTENTIAL BIODEGRADABLE IMPLANT MATERIAL: A REVIEW - Nanang Qosim; Silmina Adzhani (VANOS Journal of Mechanical Engineering Education, 2017)
As a lightweight metal with mechanical properties similar to natural bone, magnesium-based material has been gaining wide popularity. However, the applications are seriously limited due to the excessively rapid degradation rate in the physiological environment, causing the magnesium to degrade faster than the complete rehabilitation of the bone itself. Grain refinement approach is currently the selected approach to obtain a lower degradation rate without adding other element that might be harmful to human body. This paper studies the possibility of reducing biodegradation rate of a biodegradable through reviewing various studies on grain refinement through hot deformation and rapid solidification.